SOIL FUNGI PROMOTE VIGOR IN SEEDS FROM BRAZILIAN DRY SEASONAL FOREST - Ferreira, Thiago Costa; Perez-Marin, Aldrin Martin (Biofix Scientific Journal, 2022)
The Brazilian Dry Seasonal Forest (Caatinga Biome) is poorly studied about possible interactions between seeds, seedlings, and Trichoderma harzianum strains to promote vegetal vigor in seedlings. So, this research aims to study the T. harzianum strain promotion of vigor in different species from Caatinga Biome in nursery. For assays, we used: Aspidosperma pyrifolium, Cnidoscolus quercifolius, Handroanthus impetiginosus, Pseudobombax marginatum, and Tabebuia aurea species and the T. harzianum IBLF 006 based-product-inoculant. We tested these assays in nursery conditions. T. harzianum solution (0.5% v/V) was used in the nursery assay (applied over soil after the sowing). For this research, we evaluated variables of vigor and germination and there was a control treatment (non-inoculated). About nursery assay results, there was a positive interaction for all species between seeds and seedlings and T. harzianum, except for T. aurea and C. quercifolius. For all species tested in this research, we suggest that other seed or soil treatments can be tested in environmental Caatinga Biome conditions to expand this knowledge about the interaction between Trichoderma harzianum and seedlings and seeds from Caatinga biome.